Polymineraldy gave kumyn paydalan arkyly aerated concrete materialsnyn sapasyn arttyru - Iztileu, Сәбит (Рroblems of engineering and professional education, 2023)
The article deals with the production of concrete with a non-autoclaved cellular structure, which eliminates the need for expensive autoclaves, very energy- and metal-intensive, in boiler rooms producing high temperature and high pressure steam, as well as the use of substandard raw materials (polymineral barkhan sands) and various chemical additives , which allow to increase the technical and economic efficiency of the production of cellular concrete, which is a very urgent task.